MOTIVAS I ITALIC UNITED LIBERATION MOVEMENT FOR WEST PAPUA (ULMPW) DALAM MENCARI DUKUNGAN KE MELANESIA SPEARED GROUP (MSG) - Wirapranatha, Adityo; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This Research is a diplomation political study which describes the ULMWP motivation looking for support to MSG. This Research will focus on why ULMWP looking for support to MSG. This Study interesting because describe about the motivation of ULMWP looking for support to MSG and ULMWP effort to get support from MSG to reach their goals that is self-determination for West Papua.  This is qualitative research which used descriptive methods, and collecting datas from some resources like books, journals. official publication, and relevant websites. This paper used pluralism perspective, level analysis of group behavior, and separatists group concept from T. R. Gurr. The object in this research is ULMWP an main actor in International Relations. The result of this research shows that ULMWP looking for support to MSG to reach their goals from international community and get their independence from Indonesia. ULMWP has several motivations in seeking support for MSG. such as  MSG as a media voices to struggle for the movement of ULMWP,  conformity of the ULMWP and MSG in missions regarding human rights enforcement, ULMWP has race and historical proximity with MSG members, and good message from MSG Members to ULMWP regarding West Papua's self-determination.through this motivation, they tried to get support from the MSG in their goal of achieving independence from Indonesia.  Keywords : Motivation, Sepratists Movement, International Organization, Diplomation